Synthetic Aperture Radar Autofocusing Using Evolutionary Computation Tecniques - Lim, Tien Sze (2008)
A major challenge in synthetic aperture radar (SAR) system development involves compensations for undesirable variations in the azimuth SAR phase history. Primary causes of these phase variations include oscillator phase instabilities, uncompensated sensor motion and atmospheric propagation. depending on their nature and magnitude, phase errors can significantly degrade the quality of SAR images in terms of geometry linearity, resolution, image contrast and signal-to-noise ratio (SNR).